Percepciones de calidad de vida de los habitantes de San Benito (Santander) debido a la falta de acueducto (2019)
Environmental psychology is a branch of psychology, which seeks to know how environmental situations affect people's behavior, according to the environment in which they are developing, and how they adapt to the situations presented by it. This work was carried out with the objective of understanding the perceptions of quality of life of the participants of San Benito - Santander, due to the lack of aqueduct. Qualitative research was carried out, through data collection through open interviews; to 4 inhabitants of the municipality. W